HUBUNGAN ANTARA TINGKAT PENGETAHUAN TENTANG KANKER SERVIKS DAN KEIKUTSERTAAN MELAKUKAN PEMERIKSAAN INSPEKSI VISUAL ASETAT DI PUSKESMAS ALIANYANG PONTIANAK - ., Deasy Mirayashi (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Cervical cancer is the second most common cancer amongwomen in Indonesia after breast cancer and it can be prevented withregular screening uptake. Low level of women’s knowledge about cervicalcancer is one of the factor related to poor uptake of cervical cancerscreening in Indonesia. Objective: The aim of this study was to know therelation between knowledge level about cervical cancer and participationin visual inspection with acetic acid examination at Alianyang public healthcenter Pontianak. Method: This research was an analytic study with across-sectional approach and using non-probability sampling (purposivesampling) technique. Eighty-eight women aged 25-49 years wereinterviewed using questionnaire and data were analyzed using chi-squaretest. Result: Chi-square test result showed that statistically there is arelation between knowledge level about cervical cancer and participationin visual inspection with acetic acid examination (p=0,009). Conclusion:There is a relation between knowledge level about cervical cancer andparticipation in visual inspection with acetic acid examination at Alianyangpublic health center Pontianak. Keywords: Knowledge level, cervical cancer, visual inspection with aceticacid. 1) Medical School, Faculty of Medicine, Universitas Tanjungpura, Pontianak, West Kalimantan2) Department of Community Medicine, Faculty of Medicine, Universitas Tanjungpura, Pontianak, West Kalimantan3) Department of Anatomy, Faculty of Medicine, Universitas Tanjungpura, Pontianak, West Kalimantan